X-linked ichthyosis along with epidermolysis bullosa - Shambulingappa Pallagatti; Soheyl Sheikh; Anupreet Kaur; Amit Aggarwal; Ravinder Singh (Wolters Kluwer Medknow Publications, 2012)
Ichthyoses are a heterogenous group of hereditary keratinization disorders that share in common the accumulation & shedding of large amounts of hyperkeratotic epidermis.Early reports of ichthyosis in the Indian and Chinese literature date back to several hundred years. X-linked recessive ichthyosis (XLI) is a common disorder of keratinization and affects males who inherit an X-chromosome having a steroid sulphatase genetic mutation.In the present communication we report a case of XLI and dystrophic epidermolysis bullosa in the same patient. To the best of our knowledge it has been reported only once before.